THE OCCURRENCE OF GLASS EEL ( ANGUILLA SPP. ) AT CIKASO RIVER, SUKABUMI - Irsyad Zhafar, Muhammad
Eel (Anguilla Spp.) is one of the most prominent freshwater fish as consumption and export commodities. Meanwhile, in Indonesia, the aquaculture activity regarding this species is limited to the grow-out stage only. Most of them still derive the eel or glass eel (or GE) seeds from nature. GE inhabits the saltwater area. As they grow, they migrate to the river, which predominantly a freshwater environment, and continuing to grow there. Most fishers here take advantage of this migration time to catch the GE. The high dependence on the availability of seeds from nature makes the eel aquaculture industry very vulnerable. Therefore, it is necessary to do research that can support the development of eel culture. This research is about the activity of the GE during its migration process in Cikaso River. The abundance of catches overnight, environmental conditions, and body would be the representations. Cikaso River in Ciniti village, Sukabumi, was the place of the conducted research. GE activity upstream of the river was observed every 1 hour by counting the number of GEs caught with "sirib" (measuring: 1.5 × 1.5 m2, 2 mm mesh). Sampling started at 19.00 until 05.00 the next day with a total of 300 catching effort each. The GE samples obtained were preserved with 5% formalin to be taken to the laboratory and measured their length and weight. The daily activity of the GE movement is mostly at 20.00 in January. Based on the data collected, the pattern shifted in November to 21.00 and in December to 19.00. enviromental factor (water depth, current velocity, pH, DO, Salinity, Temperature, and TDS) are also taken into account. The daily activity of the GE is affected by the ebb and flow. Which conditions can be expressed by fluctuations in water level, current velocity, TDS, and salinity. In terms of shape, the GE body tends to be flat and elongated, seen from its long and heavy relationship with values varying from 1.6925 to 2.435, and the growth is negative allometric, which means eel's growth is faster than its weight gain. The R-value is from 0.2312 to 0.51.